2007
DOI: 10.1007/s11284-007-0412-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat feature, antenna position, movement, and fix interval on GPS radio collar performance in Mount Fuji, central Japan

Abstract: The location performance of a global positioning system (GPS) collar was assessed for different habitats and geographical areas. We tested the effects of habitat features, antenna position, movement, and fix interval on location performance around Mount Fuji, a single peak surrounded by wide and flat areas. Fix rate decreased from 100% in open flat areas to 53% under sloped dense canopy. The openness (the actual available sky, i.e., the percentage of a radio collar exposed to the sky when part of the collar is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 9 publications
8
57
1
Order By: Relevance
“…Excluding canopy effects, terrain complexity alone may result in an 8 per cent or less reduction in fix rates and 10-13 m measurement error on average (D'Eon et al 2002;Cain et al 2005). Collar orientation alone tends to have a negligible effect on GPS errors in open areas, but can reduce fix rates up to 80 per cent and location precision as much as 17 m under dense canopy cover (Heard et al 2008;Jiang et al 2008). Cain et al (2005) observed that reducing the frequency with which locations were collected, from every 15 -30 min to every 6-13 h, reduced fix rates up to 8 per cent without affecting location precision.…”
Section: Types Magnitude and Causes Of Gps Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding canopy effects, terrain complexity alone may result in an 8 per cent or less reduction in fix rates and 10-13 m measurement error on average (D'Eon et al 2002;Cain et al 2005). Collar orientation alone tends to have a negligible effect on GPS errors in open areas, but can reduce fix rates up to 80 per cent and location precision as much as 17 m under dense canopy cover (Heard et al 2008;Jiang et al 2008). Cain et al (2005) observed that reducing the frequency with which locations were collected, from every 15 -30 min to every 6-13 h, reduced fix rates up to 8 per cent without affecting location precision.…”
Section: Types Magnitude and Causes Of Gps Errorsmentioning
confidence: 99%
“…An interaction between movement and forest cover was observed by Jiang et al (2008) using devices affixed to a vehicle moving approximately 10 kph. Jiang et al (2008) documented reductions in both fix rates and the proportion of fixes in a three-dimensional mode when moving through forest but not through open areas.…”
Section: Types Magnitude and Causes Of Gps Errorsmentioning
confidence: 99%
“…Dataset that had GPS errors like missing coordinates were removed from the dataset before analysis. The causes of GPS errors are: Temporal malfunction of the GPS collars (Gala, 2014), canopy cover (Jiang et al, 2008;Sager-Fradkin et al, 2007;Heard et al, 2008), topography (terrain and slope; Hebblewhite et al, 2007;Frair et al, 2004) and collar orientation (Sager-Fradkin et al, 2007;Heard et al, 2008;Moen et al, 1996;Frair et al, 2010). The data available for analysis after screening ranged between 58 and 92% (Table 2), which is within acceptable range to characterize wildlife movement patterns and make sound inference (Frair et al, 2010).…”
Section: Data On Elephant Locationsmentioning
confidence: 98%
“…These problems are caused by variations in canopy closure across a landscape, by rugged topography, by changes in collar orientation with respect to GPS satellites, by fix interval, and by behavior of collared animals (Belant, 2009;Cain et al, 2005;D'Eon and Delparte, 2005;D'Eon et al, 2002;Jiang et al, 2008;Lewis et al, 2007;Mattisson et al, 2010). Missed fixes pose major problems but one can identify them from the null, default, or illogical values representing them in the data.…”
Section: Introductionmentioning
confidence: 99%